Guarantees to ensure the rights, freedoms and legitimate interests of persons in places of detention - Kuryliuk, Yu.; Kovalevska, I.; Shvedova, H.; Salaieva, K. A.; Салаєва, К. А.; Kundeus, V. G.; Кундеус, В. Г.; Vladyslav Kundeus; Салаєва Карина Анатоліївна (Revista Relações Internacionais do Mundo Atual Unicuritiba. - 2023. - Vol. 4., № 42. - Р. 613-629, 2023)
Актуальність даної теми пояснюється необхідністю вдосконалення законодавства з метою більш ефективного забезпечення прав і законних інтересів осіб, які перебувають у місцях несвободи. Права, свободи і законні інтереси затриманих і адміністративно заарештованих визначаються Конституцією України, законами, розпорядженнями Кабінету Міністрів України та правилами внутрішнього розпорядку. Одним із аспектів діяльності адміністрації місць несвободи є забезпечення реалізації прав цієї категорії громадян та осіб без громадянства. Досліджено також особливості правової реалізації органами державного управління прав і законних інтересів осіб, які тримаються в місцях примусового тримання. Досліджено способи реалізації прав, свобод і законних інтересів осіб, які перебувають у місцях примусового тримання. Автор також висвітлює зміст правового регулювання, зокрема внутрішнього розпорядку, надання медичної та правової допомоги, забезпечення санітарно-гігієнічних норм у місцях несвободи в установах МВС України. Автор підкреслює важливість нагляду та контролю для забезпечення реалізації прав затриманих та заарештованих осіб.

The relevance of this topic is explained by the need to improve legislation in order to ensure more effective exercise of the rights and legitimate interests of persons in places of detention. The rights, freedoms and legitimate interests of detainees and administratively arrested persons are determined by the Constitution of Ukraine, laws, orders of the Cabinet of Ministers of Ukraine and internal regulations. One of the aspects of the activities of the administration of places of detention is to ensure the exercise of the rights of this category of citizens and stateless persons. The author also examines the peculiarities of legal implementation of the rights and legitimate interests of persons held in places of forced detention by public administration bodies. The methods of exercising the rights, freedoms and legitimate interests of persons in places of forced detention are investigated. The author also highlights the content of legal regulation, including internal regulations, provision of medical and legal assistance, and ensuring sanitary and hygienic standards in places of detention in the institutions of the Ministry of Internal Affairs of Ukraine. The author emphasises the importance of supervision and control to ensure the exercise of the rights of detained and arrested persons.

Актуальность данной темы объясняется необходимостью совершенствования законодательства в целях обеспечения более эффективной реализации прав и законных интересов лиц, находящихся в местах лишения свободы.
Garantias para assegurar os direitos, as liberdades e os interesses legítimos das pessoas em locais de detenção
Keywords: Procedural guarantees; Places of detention; Rights, freedoms and legitimate interests; procedural guarantees; places of detention; rights, freedoms and legitimate interests; процесуальні гарантії; місця несвободи; права, свободи та законні інтереси; Україна; процессуальные гарантии; места содержания под стражей; права, свободы и законные интересы